Misrepresentation and Expectations of Misrepresentation in an Ethical Dilemma: The Role of Incentives and Temptation - Tenbrunsel, Ann E. (Academy of Management Journal, 1998)
An investigation of ethical decision making in a negotiation context revealed that focal actors' incentives influenced not only their misrepresentation, but also their expectations of their opponents' misrepresentation, suggesting that individuals hold ?motivated expectations? about their opponents. The notion that individuals engage in defensive ethics received only modest support. The incentives of opponents influenced expectations about their misrepresentation but did not impact the focal actors' misrepresentation; however, correlational data revealed a significant relationship between the opponents' temptation and the focal actors' misrepresentation that was mediated by expectations of the opponents' misrepresentation. Furthermore, temptation mediated the proposed relationships, suggesting that it may serve as an individual factor Altering the situational influence of incentives.